A frequent nonsense mutation in exon 1 across certain HLA-A and -B alleles in leukocytes of patients with acquired aplastic anemia - Hiroki Mizumaki; Kazuyoshi Hosomichi; Kohei Hosokawa; Takeshi Yoroidaka; Tatsuya Imi; Yoshitaka Zaimoku; Takamasa Katagiri; Mai Anh Thi Nguyen; Dung Cao Tran; Mahmoud Ibrahim Yousef Elbadry; Kazuhisa Chonabayashi; Yoshinori Yoshida; et al. (Haematologica, 2020)
Leukocytes that lack HLA allelic expression are frequently detected in patients with acquired aplastic anemia (AA) who respond to immunosuppressive therapy (IST), although the exact mechanisms underlying the HLA loss and HLA allele repertoire likely to acquire loss-of-function mutations are unknown. We identified a common nonsense mutation at position 19 (c.19C>T, p.R7X) in exon 1 (Exon1mut) of different HLA-A and -B alleles in HLA-lacking granulocytes from AA patients. A droplet digital PCR (ddPCR) assay capable of detecting as few as 0.07% Exon1mut HLA alleles in total DNA revealed the mutation was present in 29% (101/353) of AA patients, with a median allele frequency of 0.42% (range, 0.071% to 21.3%). Exon1mut occurred in only 12 different HLA-A (n=4) and HLA-B (n=8) alleles, including B*40:02 (n=31) and A*02:06 (n=15), which correspond to 4 HLA supertypes (A02, A03, B07, and B44). The percentages of patients who possessed at least one of these 12 HLA alleles were significantly higher in the 353 AA patients (92%, P